2008
DOI: 10.1038/sj.jid.5701033
|View full text |Cite
|
Sign up to set email alerts
|

Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis: Assessment of Medication Risks with Emphasis on Recently Marketed Drugs. The EuroSCAR-Study

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare but severe cutaneous adverse reactions (SCAR) related to a variety of medications. They have a significant public health impact because of high mortality and morbidity. A multinational case-control study conducted in Europe between 1997 and 2001 evaluated the risk of medications to induce SCAR. Cases were actively detected through a hospital network covering more than 100 million inhabitants. Three hospitalized patients per case match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
811
15
71

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 900 publications
(927 citation statements)
references
References 23 publications
30
811
15
71
Order By: Relevance
“…Previous reports in the medical literature describe similar intervals, with the greatest risk of development of SJS occurring in the first 2 months of drug treatment 1 and an interval of 4 to 28 days being the most suggestive of drug causality in SJS. 13 We found that antibiotics and anticonvulsants were the most common medications causing SJS, with trimethoprim-sulfamethoxazole and phenytoin the most common culprits in each drug class, respectively. Previous studies enumerating medications specifically associated with SJS have identified antibiotics, anticonvulsants, and nonsteroidal anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports in the medical literature describe similar intervals, with the greatest risk of development of SJS occurring in the first 2 months of drug treatment 1 and an interval of 4 to 28 days being the most suggestive of drug causality in SJS. 13 We found that antibiotics and anticonvulsants were the most common medications causing SJS, with trimethoprim-sulfamethoxazole and phenytoin the most common culprits in each drug class, respectively. Previous studies enumerating medications specifically associated with SJS have identified antibiotics, anticonvulsants, and nonsteroidal anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Among recently marketed drugs, nevirapine and lamotrigine were strongly associated with SJS, with sertraline showing a lower but still significant risk as well. 13 Our study reflects these findings, with 2 cases secondary to lamotrigine therapy and 1 case secondary to sertraline therapy. Moreover, recently reported data from the EuroSCAR study indicated that al- a BVac = basal vacuolar change; eos = eosinophils; epi = epidermis; FTN = full-thickness necrosis; HFN = hair follicle necrosis; INK = individual necrotic keratinocytes; intra = intraepidermal; lymph = lymphocytes; neut = neutrophils; mod = moderate; PA = periadnexal; PI = pigment incontinence; PK = parakeratosis; plasma = plasma cells; PTN = partial-thickness necrosis; RBC ext = red blood cell extravasation; RE = regenerating epidermis; SPV = superficial perivascular; SPVI = superficial perivascular and interstitial; sub = subepidermal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is supported by a multinational case-control study, 12 in which the numbers of individuals taking specific medications was low among 1,500 control patients hospitalized for acute conditions. Because the control patients were hospitalized, the prevalence of medication use among the controls in this study may very well have overestimated the prevalence among the general population.…”
Section: Sampling From the General Populationmentioning
confidence: 79%
“…[11][12][13] Most HSR cases occur during the first eight weeks of treatment. [14][15][16][17] HSRs refer to dose-independent, idiosyncratic, severe adverse drug reactions (ADR). 18,19 Clinically, a triad of fever, rash and organ manifestation defines a "true" HSR.…”
Section: Introductionmentioning
confidence: 99%